The Relations of depression, anxiety and daily life activity patients with different levels of severity of chronic obstructive pulmonary disease - Asuman Dolgun Taş; Ersin Akpinar (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Introduction and aim: COPD is one of the leading causes of morbidity and mortality worldwide and it leads to economic and social burdens at significant and increasing levels. We aimed to investigate the relationship between daily living activities and depression, anxiety and disease levels in patients with COPD in our study. Materials and methods: Patients diagnosed with COPD were randomly enrolled to the study who admitted to the university polyclinics. Socio-demographic information form, mMRC dyspnea scale, COPD Assessment Test (CAT), London Chest Activity of Daily Living (LCADL) scale and Hospital Anxiety and Depression Scale (HADS) were applied. The collected data were evaluated by using statistical program. Results: In the study, 119 patients were enrolled, 94 participants were male (79%) and 25 were female (21%). Thirteen people (10.9%) who never smoked during their lifetime, 67 people (56.3%) who left the cigarette and 39 people (32.8%) were still smoking from the patients who participated in the study. There were 19 clinical cases (16%) and 100 (84%) normal cases for anxiety and 35 clinical cases (29.4%) and 84 (70.6%) normal cases for depression in the whole group. The correlation coefficient between the total score of daily living activity scale and anxiety was found as r: .289, and there is a weak level meaningful relationship between them (p<0.01). The correlation coefficient between daily life activity scale total score and depression was found as r: .259 and there is a weak level meaningful relationship between them (p<0.01). The correlation coefficient between total daily activity score and CAT total score was calculated as r: .552, and there is a moderate level meaningful relationship between them (p<0.01). Conclusion: In this study, it was concluded that activity of daily living in COPD patients was weakly correlated with depression and anxiety, and moderately correlated with disease level of severity. We believe that anxiety, depression, and severity of illness affects daily life activity in COPD patients, even if they are weak or moderate needed to be treated with a holistic approach.